2020
DOI: 10.1016/j.apnum.2019.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Multi-hp adaptive discontinuous Galerkin methods for simplified P approximations of 3D radiative transfer in non-gray media

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In such cases, isotropic h-refinement may introduce more DoFs than necessary to improve solution accuracy. Anisotropic h-adaptivity can therefore contribute to improved efficiency or even faster convergence rates by introducing new unknowns in a more frugal manner [4]. Likewise, anisotropic p-adaptivity permits increasing a cell's polynomial expansion order in only one direction to drive more efficient improvements to the solution accuracy.…”
Section: A Implementation Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, isotropic h-refinement may introduce more DoFs than necessary to improve solution accuracy. Anisotropic h-adaptivity can therefore contribute to improved efficiency or even faster convergence rates by introducing new unknowns in a more frugal manner [4]. Likewise, anisotropic p-adaptivity permits increasing a cell's polynomial expansion order in only one direction to drive more efficient improvements to the solution accuracy.…”
Section: A Implementation Goalsmentioning
confidence: 99%
“…That is not to say that the necessary theoretical foundations are absent [1], [2], rather, the requisite implementation complexity has impeded adoption of these techniques. The implementation difficulties can be avoided entirely by employing triangular or tetrahedral discretizations [3] or a discontinuous Galerkin Formulation [4]; however, nonrectangular cells are sub optimal for the linear independence of unit vectors in many CEM applications, and discontinuous Galerkin formulations do not maximize per-DoF efficiency. Therefore, we explore a far less burdensome approach to Jeremiah Corrado, Jake J. Harmon, and Branislav M. Notaroš are with the department of Electrical and Computer Engineering, Colorado State University, Fort Collins, CO 80523-1373 USA (e-mail: jcorrado@rams.colostate.edu, jake.harmon@ieee.org, branislav.notaros@colostate.edu).…”
Section: Introductionmentioning
confidence: 99%
“…In [21], an adaptive mesh refinement (AMR) algorithm has been formulated and imple-mented for the RTE by minimizing the spatial discretization error. In [12], hp-adaptive DG methods have been developed for the numerical solution of simplified P N approximations of radiative transfer in non-grey semitransparent media and it has been found that it is possible to approximate the radiative field with a significantly lower computational cost than solving the equations using the conventional finite element method. In [11], hp-adaptive methods have been develop based on a short-characteristics approach embedded in the discontinuous finite element framework.…”
Section: Introductionmentioning
confidence: 99%